Comparison Branch and Bound Algorithm with Penalty Function Method for solving Non-linear Bi-level programming with application - الشمرتي حامد سعد; حربي هبـــة فاضل (Journal of Economics and Administrative Sciences, 2020)
The problem of Bi-level programming is to reduce or maximize the function of the target by having another target function within the constraints. This problem has received a great deal of attention in the programming community due to the proliferation of applications and the use of evolutionary algorithms in addressing this kind of problem. Two non-linear bi-level programming methods are used in this paper. The goal is to achieve the optimal solution through the simulation method using the Monte Carlo method using different small and large sample sizes. The research reached the Branch Bound algorithm was preferred in solving the problem of non-linear two-level programming this is because the results were better.